Treatment of the dry form of age-related macular degeneration: the studied present and promising future - N.G. Glazko; O.A. Kanaeva; M.H. Rabadanova (РМЖ "Клиническая офтальмология")
N.G. Glazko1,2, O.A. Kanaeva2, M.H. Rabadanova2 1Hospital for War Veterans No. 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Age-related macular degeneration (AMD) is the main cause of central vision loss in elder group of patients. At the same time, annually, the number of people with detected changes in the retina corresponding to different forms of macular dystrophy is steadily growing. The disease is considered to be a highly significant medical, social and economic problem, since a deterioration of the central vision negatively affects the life quality and work capacity of patients. The article presents an analysis of modern views concerning the current therapy possibilities for the dry form of AMD, including the use of nutraceuticals, consisting of lutein, zeaxanthin, mesoseaxanthin, as well as an overview of the directions of development and clinical trials. The use of lutein- and zeaxanthin-containing compounds can be recommended for prevention both the AMD progression and the presence of risk factors for its development, especially in persons over 50 years of age, as well as in the presence of high visual workload. Keywords: age-related macular degeneration, nutraceuticals, carotenoids, lutein, zeaxanthin, mesoseaxanthin. For citation: Glazko N.G., Kanaeva O.A., Rabadanova M.H. Treatment of the dry form of age-related macular degeneration: the studied present and promising future. Russian Journal of Clinical Ophthalmology. 2022;22(4):240–246 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-240-246.